2010
DOI: 10.1093/jac/dkp507
|View full text |Cite
|
Sign up to set email alerts
|

Overall survival and fungal infection-related mortality in patients with invasive fungal infection and neutropenia after myelosuppressive chemotherapy in a tertiary care centre from 1995 to 2006

Abstract: ObjectivesInvasive fungal infections (IFIs) contribute significantly to mortality and morbidity in patients receiving myelosuppressive chemotherapy for haematological malignancies. The present study investigates the overall survival (OS), infection-related mortality and changes in treatment of IFIs in our department from 1995 until 2006.MethodsOutcomes of all chemotherapy courses were retrospectively evaluated using a standard questionnaire. Modified EORTC/MSG criteria for IFIs were applied: a positive PCR res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
111
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(119 citation statements)
references
References 29 publications
5
111
1
2
Order By: Relevance
“…Studies conducted by Mulanovich VE et al, [17] and Pagano L et al, [18], on fungal pneumonia in hematological malignancies, showed that these malignancies pose an important threat for developing fungal pneumonia. Study conducted by Corinna Hahn et al, [19] in 2006, showed that the prevalence of fungal pneumonia in hematological patients vary between 2-40%, depending on their ongoing treatment protocol. Study conducted by Spomenka Ljubic et al, [14] showed that about 20-25 % of pneumonia in diabetes patients are polymicrobial in nature and fungal pneumonias are common in these patients than with control groups.…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted by Mulanovich VE et al, [17] and Pagano L et al, [18], on fungal pneumonia in hematological malignancies, showed that these malignancies pose an important threat for developing fungal pneumonia. Study conducted by Corinna Hahn et al, [19] in 2006, showed that the prevalence of fungal pneumonia in hematological patients vary between 2-40%, depending on their ongoing treatment protocol. Study conducted by Spomenka Ljubic et al, [14] showed that about 20-25 % of pneumonia in diabetes patients are polymicrobial in nature and fungal pneumonias are common in these patients than with control groups.…”
Section: Discussionmentioning
confidence: 99%
“…are the fungi most frequently involved (22). Despite major advances in diagnostic procedures and antifungal therapy in the last decade, the prognosis of IFI in the setting of hematological malignancies remains poor, with close to 50% of patients failing frontline treatment and a mortality rate in the range of 30% (12). The advent of new diagnostic tools, including serum enzyme-linked immunosorbent assay (ELISA) for GMA (18), qPCR of fungal DNA (20,27), and computed tomography of the lungs (11), has allowed early detection of IFI and prompt treatment.…”
Section: Vol 49 2011mentioning
confidence: 99%
“…12 Therefore, patients with APL on ATRA therapy may need antifungal therapy. [13][14][15] Since its discovery, in 1955, amphotericin B (AB) 16,17 remains as the antimicrobial of choice for this practice, as well as for the treatment of confirmed systemic fungal infections. 16,18 However, AB is associated with chronic and acute adverse effects, especially nephrotoxicity, which may cause renal damage and electrolytic disorder (hypokalemia and hypomagnesemia).…”
Section: 4mentioning
confidence: 99%